The HapMap project - Clark, Andrew (Henry Stewart Talks, 2007)
The problem in pedigree analysis, A possible solution for the resolution limitations in pedigree analysis, Theory of two loci, Linkage equilibrium and disequilibrium, Recombination events between SNPs, Genealogical interpretation, Statistical significance of LD, The effect of random drift on linkage disequilibrium, Variability of LD among different populations, Heterogeneity of LD across the genome, Hotspots of recombination, Tag SNPs, The HapMap website, Design of GWAS, Welcome Trust Case Control Consortium, Etiology